REDUCTION OF α, β-UNSATURATED ACIDS WITH Ni-Al ALLOY IN ALKALINE AQUEOUS MEDIUM – MECHANISTICAL ASPECTS - MIRELA SUCEVEANU; ADRIANA FINARU; SORIN I. ROSCA *2 (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The results described in the literature and our previous research confirms the efficiency of the reduction reactions of α, β-unsaturated compounds and carbonyl compounds mediated by the Ni-Al alloy in alkaline (NaOH) aqueous solution. Some particularly experiments for reduction of crotonic and cinnamic acid, was designed to bring information on the mechanism of reduction reaction with Ni-Al alloys in alkaline aqueous media. Also it was developed several deuteriation reaction of this α, β-unsaturated acids. The analysis of the isotopic distribution shows a significant and reproducible difference between Cα and Cβ that help us to draw some conclusions. In addition, recent researches give us additional arguments concerning the existence of anionic aluminum clusters with water. All this information contributes to propose a mechanism of reduction reaction and could provide new possibilities for development of this reaction: improving yield and selectivity, promoting a new synthesis etc.